Corrosion Behavior of Alloy C-276 in Supercritical Water - Hong Shi; Zhigang Gao; Zhongbiao Fan; Yuanyuan Ding; Yanxin Qiao; Zhiyuan Zhu (Advances in Materials Science and Engineering)
The corrosion behavior of Alloy C-276 in high-temperature and high-pressure water at 500°C and 25 MPa, respectively, was investigated by means of mass gain, scanning electron microscopic observation, and X-ray diffraction. The results indicated that the mass gain rate of Alloy C-276 in supercritical water obeys the parabolic law. The oxide scale was formed on Alloy C-276 with a dual-layer structure, mainly consisting of an outer Ni-rich layer and an inner Cr2O3/NiCr2O4 mixed layer. Tiny microcracks can also be found in the oxide scale if exposed for longer time. Meanwhile, higher temperature promotes oxide rate and results in thermal stress in the oxide film.